The battered who commit homicide; an overview of battered person’s syndrome and battered child syndrome in Canadian and American contexts - Mendonca, Oreen; Patel, Mitesh (Frontiers in Psychiatry, 2025)
Battered Person’s Syndrome (BPS) is a set of psychological symptoms experienced by victims who are victims of intimate partner violence. BPS may inform a defense in homicide cases wherein battered individuals killed their abusers. Similarly, Battered Child Syndrome (BCS) can be used as evidence to support a claim of self-defence wherein the child is the aggressor, and a care provider is the victim. Forensic psychiatrists provide expert opinion evidence regarding such claims of self-defence. A psycholegal opinion, often provided by forensic psychiatrists, can serve to identify factors that influence culpability and understanding of one’s actions at the material time of the offenses. Both BPS and BCS can be considered in the context of such assessments, however, further description and comparison of these syndromes is lacking in the current literature. The purpose of this article is to provide a succinct examination of the psycholegal parameters related to BPS and BCS in the Canadian and American contexts and to provide a perspective on how both can be compared. We also highlight several landmark cases in both Canada and the United States and provide a brief overview of the imperative role that forensic psychiatrists play in the development of such cases.